The comparative study on Indonesian and Japanese basic education - BP, Silvia Anggreni; Ekasyafutra, Ekasyafutra; Rusdinal, Rusdinal; Ananda, Azwar; Gistituati, Nurhizrah; Yuhasnil, Yuhasnil (International Journal for Educational and Vocational Studies, 2021)
This study aims at know the comparison of Basic Education Indonesia and Japan by using five indicators, namely the objectives of Education, education management, education budget, education personnel and salaries, and the process of evaluation of learning. The method used in this research is the study of literature with a qualitative descriptive approach to see the comparison of basic education in Indonesia and Japan, the study of literature using a qualitative descriptive approach is to gather a number of references relevant to the topic of this study. The reference is taken from national journals and international journals which are then reviewed according to the needs in this study. The results of the study shows that the comparison of Basic Education Indonesia can be seen from four aspects, namely This is due to several indicators, namely (1) differences in education objectives, (2) education management; (3) Japan Education budget; (4) his education and salary; and (5) learning processes and evaluations. This study only emphasizes on five indicators of Basic Education of Indonesia and Japan. there are gaps that can be filled by subsequent research, namely curriculum, political system, character education, and so forth. This research should contribute to the policy makers of the Indonesian Education system in order to apply the five indicators of Japanese basic education to the Indonesian basic education system.